EGFR T790M-Positive Lung Adenocarcinoma Metastases to the Pituitary Gland Causing Adrenal Insufficiency: A Case Report. (31st May 2018) - Adashek, Michael L.; Miller, Kenneth; Silpasuvan, Arit A.
Abstract : A 64-year-old man, with history of micropapillary thyroid cancer and epidermal growth factor receptor-positive lung adenocarcinoma with no evidence of active disease for 3 years after chemotherapy and radiation on erlotinib, presented with fatigue, nausea, lack of appetite, and xeroderma. A screening magnetic resonance image of the patient's head demonstrated a new bilateral pituitary mass. Initial evaluation revealed low morning cortisol, and the patient was diagnosed with adrenal insufficiency. His symptoms rapidly improved with maintenance glucocorticoids. Soon thereafter, the patient developed an acute visual deficit secondary to enlargement of the pituitary mass, and biopsy revealed EGFR T790M positive metastatic lung adenocarcinoma. Hence, we present a rare case of metastatic lung adenocarcinoma to the pituitary causing secondary adrenal insufficiency.